2015
DOI: 10.3762/bjnano.6.224
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical coating of dental implants with anodic porous titania for enhanced osteointegration

Abstract: SummaryClinical long-term osteointegration of titanium-based biomedical devices is the main goal for both dental and orthopedical implants. Both the surface morphology and the possible functionalization of the implant surface are important points. In the last decade, following the success of nanostructured anodic porous alumina, anodic porous titania has also attracted the interest of academic researchers. This material, investigated mainly for its photocatalytic properties and for applications in solar cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…The P contamination appearing at a concentration of ~11 at% in both Figure 3b,e, is due to the phosphate anions PO 4 − − entrapped in the porous oxide during its growth [18]. In both Figure 3b,e, the presence of Ti oxide grown on the surface is confirmed, as the O contents significantly increased with respect to Figure 1c from ~3 to at least ~7 at%.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The P contamination appearing at a concentration of ~11 at% in both Figure 3b,e, is due to the phosphate anions PO 4 − − entrapped in the porous oxide during its growth [18]. In both Figure 3b,e, the presence of Ti oxide grown on the surface is confirmed, as the O contents significantly increased with respect to Figure 1c from ~3 to at least ~7 at%.…”
Section: Resultsmentioning
confidence: 86%
“…However, optimal roughness values and surface morphology pattern are still controversial and need to be more clearly defined [2,15]. One current hypothesis is that to augment implant surface bioactivity and promote both early integration and long-term success, dental implant surface should carry both macro, micro and nanoscale features and related roughness [16,17,18]. While the macroscale shape depends on machining, and the microscale roughness can be successfully obtained by etching or sand-blasting, it has been shown that anodization is an effective means to obtain nanoroughness, in the form of anodic porous titania (APT).…”
Section: Introductionmentioning
confidence: 99%
“…The area of the bone-to-implant interface can be extended by increasing the implant surface roughness, resulting in an improvement in the primary stability of the implant [ 15 , 16 ]. In addition, implants with increased surface roughness promote osseointegration between the implant and bone, thus reducing the waiting period for bone healing before loading [ 17 , 18 ]. Recently, efforts have been made to minimize the time when stability dips occur by increasing hydrophilicity or bioactivity of the implant surface to promote blood clot formation around the implant and growth factors to move around the implant [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of materials with tailored porosity and pore size has attracted considerable attention for their promising potentials in electrocatalysis, sensing, scaffolds, and capacitors [ 1 , 2 , 3 , 4 , 5 , 6 ]. Among many porous materials studied, the inverse opals—also known as the 3D ordered macroporous materials—have received the most scrutiny because their macropores are arranged in a honeycombed structure with 12 pore channels connecting neighboring macropores [ 7 ].…”
Section: Introductionmentioning
confidence: 99%